2022
DOI: 10.13057/asianjethnobiol/y050104
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants used by local people of Mojana Wadera Woreda, North Shewa Zone, Amhara Region, Ethiopia

Abstract: Abstract. Haile AA. 2022. Ethnobotanical study of medicinal plants used by local people of Mojana Wadera Woreda, North Shewa Zone, Amhara Region, Ethiopia. Asian J Ethnobiol 5: 35-43. This study was conducted in Mojana Wadera Woreda of North Shewa Zone (Ethiopia) to document the indigenous knowledge of local communities on medicinal plants. The data was collected using structured and semistructured interviews with herbalists. Information on medicinal plants was collected from June 2020 to October 2020. Fourtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In this study, traditional healers prepare ethnoveterinary recipes mostly in the forms of pounding and homogenizing with water followed by crushing. This finding is in agreement with those (Legesse;2010;Lulekal et al, 2014;Eshetu et al, 2015) who reported pounding the remedial part and homogenizing it with water was found to be the major mode of remedy preparation. The present study showed that the claimed medicinal plants have values other than their medicinal roles.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, traditional healers prepare ethnoveterinary recipes mostly in the forms of pounding and homogenizing with water followed by crushing. This finding is in agreement with those (Legesse;2010;Lulekal et al, 2014;Eshetu et al, 2015) who reported pounding the remedial part and homogenizing it with water was found to be the major mode of remedy preparation. The present study showed that the claimed medicinal plants have values other than their medicinal roles.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the botanical families with the highest number of medicinal plant species were Asteraceae and Lamiaceae, followed by Rosaceae, Polygonaceae, Ranunculaceae, and Solanaceae. Asteraceae as a dominant family in such type of studies has been previously reported in other parts of the world [27,28]. The possible reason behind the dominance of this family might be its extensive distribution, abundance, and richness in the study area [26].…”
Section: Disease Categorysupporting
confidence: 56%
“…Rich) Guill. and Perr [ 23 ], Artemisia abyssinica [ 24 26 ], Balanites aegyptiaca (L.) Delile [ 21 ], Calpurnia aurea (Ait). Benth [ 20 , 22 , 29 , 30 , 32 , 35 , 36 ], Carica papaya L. [ 28 ], Carissa spinarum L. [ 26 , 29 , 30 ], Clutia abyssinica Jaub.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ], Leonotis ocymifolia [ 28 , 35 , 36 ]. Lepidium sativum L. [ 26 , 28 30 ], Linum usitatissimum L. [ 22 , 24 ], Malva parviflora L. [ 21 ], Mentha piperita L. [ 21 , 25 ], Momordica foetida Schumach [ 20 ], Myrtus communis L. [ 34 ], Ocimum lamiifolium L. [ 29 , 30 ], Gossypium barbadense L. [ 37 ], Plectranthus lactiflorus (Vatke) Agnew [ 26 ], Prunus persica (L.) Batsch [ 20 ], Punica granatum [ 32 ], Rumex abyssinicus [ 27 ], Rumex nepalensis (Spreng) [ 38 ], Ruta chalepensis L. [ 24 , 29 , 30 ], Salvia nilotica Jacq. [ 22 ], Satureja punctata R. Br.…”
Section: Resultsmentioning
confidence: 99%